OUTSOURCING AS A KEY COMPONENT OF MODERN BUSINESS: NEW PERSPECTIVES AND SCIENTIFIC APPROACHES - Razzakov Kuvonchbek Anvar ugli; Iskandarov Xumoyun Sevdiyor ugl (Innovation Science and Technology, 2025)
In the era of rapid digital transformation and economic globalization, outsourcing has transitioned from a costreduction mechanism to a strategic lever for business innovation and growth. Traditional outsourcing models, which focused on delegating non-core operational tasks, have been superseded by Cognitive Outsourcing (CO a new paradigm that integrates artificial intelligence (AI), machine learning (ML), predictive analytics, and automation with external expertise to enhance organizational agility and decision-making capabilities. This study introduces Cognitive Outsourcing as an evolving business model that not only delegates operational processes but also strategic decision-making to external providers empowered by advanced technologies. This paper presents a comprehensive framework for Cognitive Outsourcing and examines its applications, challenges, and implications for modern businesses. By analyzing empirical data and industry case studies, this paper contributes new insights into how organizations can harness this emerging model to gain a competitive edge while addressing the critical issues of data security, regulatory compliance, and ethical considerations in AI-driven decision-making.